Pediatric visceral leishmaniasis: diagnosis and therapy - O. V. Samodova; I. I. Volkova; G. P. Smirnova; T. V. Pyatlina; E. I. Smetanina; Yu. L. Khovanova; A. V. Morozova (Журнал инфектологии)
Visceral leishmaniasis is a generalized infection of the reticuloendothelial system, it is fatal if left untreated in most cases. Early diagnosis and effective therapy can reduce the risk of disability and mortality. However, in non-endemic areas diagnosis may be delayed or missed. In the article we presented a case report of a child with imported visceral leishmaniasis. The gradual onset of the disease with irregular fever, growing weakness, fatigue, loss of appetite, anemia, cytopenic syndrome required differential diagnosis with oncological diseases. The diagnosis of leishmaniasis was made by microscopy of a bone marrow smear and the detection of leishmania. Recovery occurred after the prolonged course of amphotericin B and supportive treatment.